ANTIOXIDANT AND EFFECTS OF PROCESSING USING BIXIN POTASSIUM SALT AS A NITRITE REPLACEMENT IN RESTRUCTURED MEAT PRODUCTS - GOLIN PACHECO, Samanta Daliana; GARCIA, CARLOS EDUARDO ROCHA; ARLORIO, MARCO; WAGNER, RICARDO; STRAPASSON, GIOVANNA; MASSON, MARIA LUCIA; OCAMPOS, FERNANDA; BARISON, ANDERSON; PASQUINI-NETTO, HARLI; DECASTELLI, LUCIA; et al. (Visão Acadêmica, 2018)
This study aimed to evaluate bixin potassium salt as a replacement for sodium nitrite (NaNO2) in restructured meat products. Bixin was obtained from the chloroform extract of annatto seeds using a Soxhlet apparatus. Restructured meat samples were prepared using raw retail cuts of beef (vastus lateralis), stored at −16º C, and evaluated during storage at 60 days. The efficacy of bixin potassium salt as a NaNO2 replacement in restructured meat was evaluated by measuring residual concentrations of TBARS, color (L*, a*, and b* components), a sensory preference test, and microbiological parameters. Bixin potassium salt proved to be a viable alternative to nitrites for preserving the color and inhibiting the oxidative degradation of restructured meat. The outcomes showed that the effect of bixin potassium salt on microbiological stabilization was quite variable, depending on the bacterial species considered.